Droit colonial et anthropologie. Expertises ethniques, enquêtes et études raciales dans l’outre-mer français (fin du xixe siècle-1946) - Silvia Falconieri (Clio@Themis)
In the context of 19th- and 20th-century French colonialism, anthropological knowledge plays a crucial role when it comes to legally categorising colonised populations. What are the forms, modalities and aims at stake when the law encountered that other knowledge ? What is the anthropology of colonial legal experts ? How are the knowledge, tools and techniques of anthropology mobilised by colonial jurists, and what are the consequences ? In the light of these questions, this article tackles the issues at stake when colonial law met physical and racial anthropology in the shaping of the statuses of subject and citizen in the French Empire. The analysis of the particular case of the non-recognised Métis being granted French citizenship shows that specialists in colonial law made extensive use of contemporaneous anthropological studies. Not only did they appropriate the contents of anthropological research, but they also learned a method which was to be mobilized in the judicial proceeding. In the 1920s, « ethnic expertise » and investigation became the pillars of a new legal proceeding that was, in large part, the result of the rapprochement of colonial law and racial anthropology.